E-Komik Bahasa Indonesia berbasis Android dengan Pendekatan Konstruktivisme untuk Siswa Sekolah Menengah Pertama - Arifin Tahir; La Ode Muhammad Ruspan; Muhlis Tahir (Universitas Hamzanwadi, 2023)
The limitations of learning media in the teaching and learning process make it difficult and difficult to create learning media and have difficulty choosing media that suits the learning conditions experienced at SMPN 5 Kendari. This research aims to develop e-comic learning media with a constructivist learning approach for students of SMP Negeri 5 Kendari class VII semester 1. Apart from that, this research also uses the SPRINT method in making e-comics with stages namely understand, diverge, decide, prototype, and at the validate stage using ISO 25010 testing on the aspects of functional suitability, performance efficiency, usability, maintainability and portability. The result of this research is an application as an e-comic based learning media for middle school students in class VII semester 1. In addition, there are test results in the form of ISO 25010 testing from media experts which are declared very feasible with a percentage of 95.26%. Then a small group trial test was also carried out which got 93.33% and a large group CBA test of 91.86%. After testing this group, the percentage of students' completeness in understanding learning outcomes using e-comics was 78.68%. Therefore, it can be concluded that e-comics developed using the SPRINT model and constructivist approach are able to increase the effectiveness of Indonesian language learning at SMP Negeri 5 Kendari class VII.